2018
DOI: 10.1111/epi.14460
|View full text |Cite
|
Sign up to set email alerts
|

Evolution over time of SUDEP incidence: A nationwide population‐based cohort study

Abstract: Prompted by a recent report on declining incidence of sudden unexpected death in epilepsy (SUDEP) following implantation of a vagus nerve stimulator (VNS), we analyzed SUDEP risk over 6 years in a population-based cohort of 60 952 epilepsy patients in Sweden. All deaths from July 1, 2006 through December 31, 2011, were identified. Those with epilepsy mentioned on the death certificate were adjudicated for SUDEP using medical records and autopsy reports. In all, 292 SUDEP cases were identified. Comparing the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 14 publications
2
27
0
5
Order By: Relevance
“…However, the audit of 466 VNS cases enrolled at a single center showed that patients with VNS carried a similar risk for SUDEP as other drug refractory patients [ 87 ]. Tomson and Ryvlin suggested that the risk of SUDEP significantly decreases during long-term follow-up in VNS therapy [ 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the audit of 466 VNS cases enrolled at a single center showed that patients with VNS carried a similar risk for SUDEP as other drug refractory patients [ 87 ]. Tomson and Ryvlin suggested that the risk of SUDEP significantly decreases during long-term follow-up in VNS therapy [ 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some data suggest that it might reduce the risk of SUDEP [121,122], but not consistently [123]. Furthermore, studies reporting a decline of SUDEP during follow-up lack a control group [122], thus making it impossible to ascribe this effect to VNS treatment or simply to the natural course of SUDEP risk, which other studies have shown to be decreasing overtime with duration of follow-up [124].…”
Section: Preventionmentioning
confidence: 99%
“…43. In addition, a large study from Sweden of 57,775 people with epilepsy found the incidence of SUDEP (again in prevalent cases) to be similar across the ages. 47 From the perspective of transition, it would seem prudent to consider SUDEP as an important topic to emphasize as the youth takes responsibility for factors in their control to concentrate on the importance of good seizure control.…”
Section: Sudep (Sudden Unexpected Death In Epilepsy)mentioning
confidence: 99%